2013
DOI: 10.1002/biof.1063
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and neurodegenerative diseases

Abstract: Over the last ten years curcumin has been reported to be effective against a wide variety of diseases and is characterized as having anti-carcinogenic, hepatoprotective, thrombosuppressive, cardioprotective, anti-arthritic, and anti-infectious properties. Recent studies performed in both vertebrate and invertebrate models have been conducted to determine whether curcumin was also neuroprotective. The efficacy of curcumin in several pre-clinical trials for neurodegenerative diseases has created considerable exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 134 publications
1
88
0
1
Order By: Relevance
“…Up until now, clinical trials carried out on humans affected by AD or by mild cognitive impairment have not provided results corroborating Cur efficacy, but several studies are still ongoing (for a review, see [205]).…”
Section: The Anti-amyloid Properties Of Natural Phenols and Polyphmentioning
confidence: 99%
“…Up until now, clinical trials carried out on humans affected by AD or by mild cognitive impairment have not provided results corroborating Cur efficacy, but several studies are still ongoing (for a review, see [205]).…”
Section: The Anti-amyloid Properties Of Natural Phenols and Polyphmentioning
confidence: 99%
“…Curcumin was reported to affect the amyloidb pathway by reducing the formation of amyloid-b fibrils and inhibiting its aggregation (Sahni et al, 2011). It also exhibits cytoprotective and anti-inflammatory properties through protection of the cells against amyloid-b-induced toxicity and reduction of the expression of cytokines and chemokines, with improvement in memory and cognitive defects, leading to reversal of neurodegeneration (Agrawal et al, 2010;Sahni et al, 2011;Monroy et al, 2013). Similarly, resveratrol was reported to affect the amyloid-b pathway by reducing the production of amyloid-b peptides and remodeling of the soluble oligomers and fibrils into non-toxic forms of amyloid-b, in addition to its cytoprotective actions and reduction of cognitive defects (Sahni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that those who consumed curry very often, at least once a week had better cognition which is different from a previous study, which noted that regular use of low or moderate curry consumption, at least once in six months had significant effect on cognition 12 . An experimental study with rats reported that low dose of curcumin reduced ÎČ-amyloid and plaque burden 6 . This could be the plausible reason for the cognitive protection of curcumin.…”
Section: Resultsmentioning
confidence: 99%